Enhancement of thermal and flow characteristics in helically coiled tubes with corrugated surfaces by Genetic Algorithm based optimization - Kirkar, Safak Metin; Gonul, Alisan; Dalkilic, Ahmet Selim (ELSEVIER SCIENCE INC, 2024)
This study investigates the combined use of helically coiled tubes and corrugated surface structures as two different heat transfer enhancement techniques. Both the curvature ratio and corrugation form swirl and secondary flows, resulting in higher heat transfer rates. The effects of pitch and depth of corrugation on the performance evaluation criteria, Nusselt number, and friction factor are studied parametrically at different Reynolds numbers. A multi -objective optimization is performed to obtain the best thermal-hydraulic performance, and a sensitivity analysis is conducted to investigate how wall corrugation specifications affect performance. The numerical results indicate that corrugated helically coiled tubes have significantly higher thermal and hydraulic performance at Reynolds numbers lower than 2300 compared to smooth plain tubes. The corrugated coiled tubes can improve Nusselt numbers by up to 7.39, 2.02, and 1.84 compared to the smooth plain, corrugated plain, and smooth coiled tubes of the same size, respectively. They can also improve friction factors by up to 33.26, 1.82, and 10.42, and performance evaluation criteria by up to 2.83, 1.66, and 1.09. The proposed novel correlations are the first and fourth in the literature, respectively, for predicting the Nusselt number and friction factor of corrugated helically coiled tubes. Based on 240 data points that were acquired via parametric and optimization studies, these correlations have been established within 10% error margins.
Keywords: Helically coiled tube; Corrugated surface; Heat transfer augmentation; Genetic Algorithm; Optimization; Response Surface Methodology; HEAT-TRANSFER CHARACTERISTICS; PRESSURE-DROP; LAMINAR-FLOW; EXCHANGER; PERFORMANCE; STRAIGHT; Thermodynamics; Engineering; Mechanics